The Utilization of Calcined Green Mussel Shell as Partial Cement Replacement on Compressive Strength of Mortar - Muhamad Zulfikar Zakaria; Eva Arifi; Devi Nuralinah; Rudianto; Sugeng P.Budio; Retno Anggraini; Achfas Zacoeb (Jurnal Mahasiswa Jurusan Teknik Sipil, 2023)
Abstract. In this research, an innovation to support the utilization of green mussel shells waste in the Gresik area, specifically in Banyu Urip village has been conducted. Green mussel shells have a high calcium carbonate (CaCO3) content. Calcium carbonate can be utilized as a partial replacement material in mortar. Mortar is a paste-shaped mixture consisting of cement, sand and water. In one of the mortar mixtures, cement has a dominant calcium oxide compound content. Calcium oxide can be obtained from the calcination process of calcium carbonate (CaCO3). Calcination of calcium carbonate occurs through the process of decomposing calcium carbonate (CaCO3) compounds into calcium oxide (CaO) compounds through heat treatment at high temperatures. Therefore, the content contained in green mussel shells can be used as a substitute for some mixtures in mortar. This research aims to determine the compressive strength of mortar. This research methodology uses experimental methods in the laboratory. In the heat treatment process, the temperature used was 900°C for two hours. The calcium oxide obtained from the process was mixed into the mortar using the weight ratio of cement. The test specimens used were 5cm x 5cm x 5cm cubes, with the cement replacement percentage determined as 10%, 20%, and 30%. The results obtained in the compressive strength test decreased as the percentage of the mixture in the mortar increased. Keywords: Green Mussel Shell Waste, Cement Replacement, Compressive Strength, Sustainable Construction